SENSE: Pendampingan Peningkatan Keterampilan Sosial Emosional melalui Theater Based Intervention - Tiara; Mutiara; Septia, Hidayatul Dwi; Hariadi, Rudi; Suliyanto; Nasution, Riska Amalya (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Abstract SENSE Program: Assistance in Improving Social Emotional Skills through Theater Based Intervention aims to improve the social and emotional skills of children with Autism Spectrum Disorder (ASD). This service was carried out at SLB Harapan Mulia Jambi involving 22 autistic children, using the Theater Based Intervention method which involves theater activities and educational games such as freeze dance, paper sensory, Simon says, and emoticon block. The program was implemented with a pre-experimental approach, using a One Group Pretest-Posttest design to evaluate changes in social and emotional skills before and after the intervention. Results showed a significant improvement in children's social and emotional skills after participation in the activities. Statistical test results with a significance value (p = 0.000 < 0.05) confirmed that the theater intervention was effective in improving communication skills, emotion control, and social interaction of children with ASD. Thus, Theater Based Intervention proved to be an efficient approach for the social-emotional development of children with autism. Keywords: Autism Spectrum Disorder, social emotional skills, theater intervention, children with autism, self-development. Abstrak Program SENSE: Pendampingan Peningkatan Keterampilan Sosial Emosional melalui Theater Based Intervention bertujuan untuk meningkatkan keterampilan sosial dan emosional anak-anak dengan Autism Spectrum Disorder (ASD). Pengabdian ini dilakukan di SLB Harapan Mulia Jambi dengan melibatkan 22 anak autis, menggunakan metode Theater Based Intervention yang melibatkan aktivitas teater dan permainan edukatif seperti freeze dance, paper sensory, Simon says, dan emoticon block. Program ini dilaksanakan dengan pendekatan pre-eksperimental, menggunakan desain One Group Pretest-Posttest untuk mengevaluasi perubahan keterampilan sosial dan emosional sebelum dan sesudah intervensi. Hasil menunjukkan adanya peningkatan signifikan dalam keterampilan sosial dan emosional anak setelah partisipasi dalam kegiatan. Hasil uji statistik dengan nilai signifikansi (p = 0,000 < 0,05) menegaskan bahwa intervensi teater efektif dalam meningkatkan kemampuan komunikasi, kontrol emosi, dan interaksi sosial anak-anak dengan ASD. Dengan demikian, Theater Based Intervention terbukti menjadi pendekatan yang efisien untuk pengembangan sosial-emosional anak-anak autisme. Kata Kunci: Autism Spectrum Disorder, keterampilan sosial emosional, intervensi teater, anak autisme, pengembangan diri